Analysis of carotenoid profile changes and carotenogenic genes transcript levels in Rhodosporidium toruloides mutants from an optimized Agrobacterium tumefaciens‐mediated transformation method. (22nd May 2020) - Sun, Zeping; Lv, Jing; Ji, Chaofan; Liang, Huipeng; Li, Shengjie; Yang, Zhaoxia; Xu, Wenhuan; Zhang, Sufang; Lin, Xinping
Abstract: Rhodosporidium toruloides has been reported as a potential biotechnological microorganism to produce carotenoids. The most commonly used molecular and genetic manipulation methods based on Agrobacterium ‐mediated transformation (ATMT). However, this method was of relatively lower transformation efficiency. In this study, we optimized the ATMT method for R. toruloides on account of the promoter on T‐DNA, the ratio of A. tumefaciens to R. toruloides NP11, acetosyringone concentration, cocultivation temperature and time, and a transformation efficiency of 2, 369 cells per 10 5 recipient cells was obtained and was 24 times as that of the previous report. With this optimized method, four redder mutants and four yellower mutants were selected out with torularhodin and β‐carotene production preference, respectively. The highest torularhodin production was 1, 638.15 µg/g dry cell weight in A1‐13. The yellower mutants were found to divert the metabolic flux from torularhodin and torulene to γ‐carotene and β‐carotene, and the proportion of γ‐carotene and β‐carotene were all over 92%. TAIL‐PCR was carried out to found T‐DNA insertion in these mutants, and insertion hotspot was found. RT‐qPCR results showed that CTA 1 genes in these mutants were closely related to the synthesis of total carotenoids, especially torularhodin, and was a potenial metabolic engineering site in the future. Abstract : Carotenoid and Carotenogenic Levels in R. toruloides mutants.